Supply, installation, testing & commissioning of 1MW photovoltaic solar power generation plant system with all necessary accessories for Brac University new campus building at holding no. Kha 224, Merul Badda,Dhaka-1212. - Brac University (Brac University, 2023)
This agreement made between Brac University and Bengal Renewable Energy Ltd.to supply, installation, testing & commissioning of 1MW photovoltaic solar power generation plant system with all necessary accessories for Brac University new campus building project.